Pengaruh Pupuk Kandang Sapi Dan Pengurangan Dosis NPK 16-16-16 Terhadap Pertumbuhan Dan Produksi Tanaman Cabai Rawit (Capsicum Frutescens L.) - Ramadhani Firdaus; Anggi Indah Yuliana; Mohamad Nasirudin (CV. SINAR HOWUHOWU, 2026)
This study aimed to evaluate the effectiveness of PT Petrosida Gresik's pesticide products, namely Prassida, Cozene, and Kalsida, in controlling weeds and diseases in rice cultivation through demonstration spraying (demspray) activities, as well as to assess supporting activities such as agricultural kiosk penetration and farmer outreach programs. The study was conducted during an internship program from November 2025 to March 2026 in Benjeng and Balongpanggang Districts, Gresik Regency, East Java. The methods employed included field observations, farmer interviews, direct product application in farmers’ fields, and monitoring and evaluation on the third and seventh days after spraying. The results showed that Prassida effectively controlled various weed species in rice fields, as indicated by chlorosis symptoms appearing on the third day and a significant reduction in weed populations on the seventh day after application. Meanwhile, the combination of Cozene and Kalsida effectively suppressed the development of bacterial leaf blight disease, as demonstrated by the inhibition of disease progression and the growth of healthier new leaves. In addition to demspray activities, agricultural kiosk penetration and farmer socialization programs successfully improved farmers’ knowledge regarding the proper use of agricultural products, appropriate application techniques, and effective pest and disease management strategies. Overall, PT Petrosida Gresik’s products demonstrated good effectiveness in supporting weed and disease control in rice cultivation and contributed to enhancing farmers’ understanding of sustainable and efficient agricultural practices.